Traitements non funéraires du cadavre : questions méthodologiques, identification archéologique et pistes interprétatives - Aurore Schmitt; Élisabeth Anstett; Aurélien Baroiller; Reine-Marie Bérard; Bruno Boulestin; Alexia Lattard; Hélène Ménard; Catherine Rigeade (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Many studies have addressed the issue of deviance from a funerary "norm", focusing on specific chronological periods. But the absence of any funerary treatment is underestimated in archaeological contexts and still unexplored, even though it may contribute to discussions on the functioning of past societies. Drawing on numerous cross-cultural examples through an interdisciplinary and transchronological approach, our project addresses three lines of research: the causes of an absence of funerary rites, the treatment of the remains concerned and the archaeological signature of this treatment. We have shown, among other things, that for "bad deaths", the same causes can lead to either a total absence or an alteration of funerary rites. Furthermore, a "positive" treatment of the remains of certain individuals for whom there is no prescribed funerary treatment raises the question of the value of such a practice. It has also become clear that no treatment of the corpse is specific to the absence of funerary rites, even if some treatments are frequently correlated with an absence of rites. Finally, we propose an aid to identify, label and interpret archaeological cases whose characteristics deviate from the variability of known funerary practices for a given context.